PENERAPAN STRATEGI DESIGN A TEST UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI MATERI MENGENAL RASUL - RASUL ALLAH PADA SISWA KELAS V SD NEGERI 002 LOGAS KECAMATAN LOGAS TANAH DARAT - Feni Elma Murti; Sopiatun Nahwiyah; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
Preliminary observations made by researchers in the learning process of PAI and Budi Pekerti in fifth grade students in SD2 002 Logas, Logas Tanah Darat Subdistrict, Kuantan Singingi District, showed the following symptoms or phenomena: From 15 students when there were only 8 daily tests (53.34%) who scored above the established KKM, which is 75, while others (46, 66%) value is still incomplete. When given test questions, only 60% of all students can answer the questions correctly. Each time given a homework assignment, the average student grade still gets low marks, this is seen when examined together only 53.34% of the majority of students can answer the assignment correctly. Although it has been taught about the subject of morals, but student behavior has not shown significant change. When remedial was held for the second time it turned out that there were still scores of students under the KKM 75. This study aimed to find out the application of the design a test strategy to improve learning outcomes in Islamic religious education subjects and Budi Pekerti material Getting to Know the Apostles of Allah class students V State Elementary School 002 Logas Logas Tanah Darat District.Based on the results of data collection by means of observation, interviews and documentation, then the data were analyzed descriptively-qualitative through diagrams or graphs and it can be concluded that the Application of Design A Test Strategy can improve the learning outcomes of Grade V students in Islamic Religious Education and Culture Allah's Apostles in State Elementary School 002 Logas, District of Logas Tanah Darat, this is proven by an increase in student learning outcomes ranging from pre-Cycle to Cycle III with a percentage of 73.91 (pre-cycle), 75.66 (Cycle I), 78, 41 (Cycle II) and 84.41 (Cycle III). So student learning outcomes V at SD2 002 Logas continue to increase according to the results of the evaluation of the percentage increase from cycle I to Cycle II is 2.75% and from Cycle II to Cycle III is 6%